Hypertensive Crisis in a Pediatric Patient Experiencing Clonidine Withdrawal - Can Cao; Matthew L. Lorenz; Phillip Sojka; Allison W. Brindle; Lisa Swartz Topor (Hindawi Limited, 2022)
Background. Clonidine, a central alpha-adrenoreceptor agonist, was initially developed as an antihypertensive. Though no longer commonly used for its original indication due to rebound hypertension after discontinuation, it is currently widely prescribed as a treatment for many pediatric indications including sleep disorders, behavioral concerns, and attention deficit hyperactivity disorder. Case Report. We describe a girl who developed prolonged symptoms of clonidine withdrawal, including hypertension and elevated serum metanephrines. Discussion. Clonidine withdrawal in pediatric patient can present with hypertensive urgency and other signs of sympathetic stimulation. Withdrawal can also lead to dramatic elevation in serum metanephrines. Treatment with a clonidine taper will reduce development of withdrawal symptoms. Conclusion. Given the rise in clonidine use in pediatric patients, clinicians should be aware of the risk of clonidine withdrawal and how to recognize and avoid its development.